Is clozapine to blame for delayed Ogilvie syndrome and gastrointestinal bleeding in overdose settings? - Mijatović-Jovin Vesna M.; Perković-Vukčević Nataša R.; Vuković-Ercegović Gordana N.; Đorđević Snežana B.; Vučinić Slavica S.; Šegrt Zoran P.; Kolarš Bela Š.; Jović-Stošić Jasmina V. (Srpsko lekarsko drustvo, 2022)
Introduction: Ogilvie syndrome and gastrointestinal bleeding as complications after reversal of typical clinical picture of acute Clozapine overdose is described. Case Report: A previously healthy 31-year-old man was found unconscious with Glasgow Coma Score of 6, non-reactive miotic pupils, hypersalivation and heart rate of 115 bpm. In the blood, the presence of Clozapine, Diazepam, haloperidol and biperiden were confirmed. The patient was referred to the intensive care unit for symptomatic and supportive treatment. Clinical signs registered on admission, except for sinus tachycardia, were completely resolved by the day 3. The patient began to eat and had regular bowel movements. From the seventh day, gastrointestinal complications were noticed. Nonobstructive dilatation of the stomach and intestine was confirmed on computed tomography scan. Nasogastric suction, the usage of laxatives and prostigmin injections as well as colonic irrigation was performed with a good clinical response. Conclusion: Clinicians should be aware of the potential of atypical antipsychotics to cause ileus, particulary in combination with other drugs with antimuscarinic properties, and ready to rapidly detect and treat intestinal atony thus preventing life-threatening complications. Serum Clozapine levels may not equate to clinical toxicity and the drug-näive patient require more careful observation for complications in Clozapine toxicity settings.